Industrial decarbonisation in a fragmented world: an effective carbon price with a "climate contribution" - Karsten Neuhoff; Misato Sato; Fernanda Ballesteros; Christoph Böhringer; Simone Borghesi; Aaron Cosbey; Katsuri Das; Roland Ismer; Angus Johnston; Pedro Linares; Sini Matikainen; Stefan Pauliuk; et al. (Grantham Research Institute on Climate Change and the Environment, 2025)
Context and problem The European Union's Carbon Border Adjustment Mechanism (CBAM) was introduced to prevent carbon leakage, and to incentivise global carbon pricing. The UK is set to introduce a CBAM in 2027 for the same reasons. However, this policy measure will face limitations in a fragmented geopolitical environment if progress on global carbon pricing remains slow. The reliance on international progress in carbon pricing exposes European climate and industrial policies to external risks, threatening investment certainty and decarbonisation goals. The current transition period for the EU's CBAM, in which free allocation of emissions allowances is in place until 2034, creates funding and incentive gaps for green industrial investments. Proposal for a climate contribution A straightforward charge in the form of a `climate contribution' would complement emissions trading and the CBAMs. It would be non-discriminatory, as it would be levied on domestically produced and imported carbon-intensive basic materials like steel, cement and plastic, and be based on standardised values equal to the value of free allowance allocation to conventional production. Unlike a CBAM, the climate contribution would be product-based, thus a relief for exports would be possible, in line with World Trade Organization (WTO) rules. The standardised value avoids resource shuffling and allows consistent application along the value chain. The climate contribution could help fill the funding gap left by free allocation, ensuring stable revenues to finance, for example, Carbon Contracts for Difference (CCfDs), which are critical for green industrial investments. It offers the flexibility to extend free allocation if progress in advancing global carbon pricing proves slow, without compromising climate and industrial objectives. We recommend introducing the climate contribution as a bridging instrument to complement emissions trading and ensure investment stability and incentives for green industry during the CBAM transition period. In summary, the climate contribution provides a practical, WTO-compliant solution to address carbon leakage risk, ensure investment stability, and support industrial decarbonisation in the face of global policy fragmentation.
Keywords: 330